Case Report: IgG4-RD-related ophthalmopathy combined with monoclonal gammopathy of undetermined significance - Liang, Shanshan; Xu, Wei; Zhong, Peiying; Tao, Chuanmin; Zhang, Li; Jia, Chengyao (Frontiers in Immunology, 2025)
IgG4-related disease (IgG4-RD), an immune-mediated fibroinflammatory disorder, has few reports in combination with monoclonal gammopathy of undetermined significance (MGUS). Herein, we present a case of a 69-year-old woman with manifestations of left orbital occupation and visual acuity decline. Ancillary tests indicated persistent positivity of IgG4 antibody, and IgG4-RD-related ophthalmopathy was diagnosed based on the criteria. Concurrently, serum protein electrophoresis revealed an M protein level of 12.23 g/L. Immunofixation electrophoresis suggested a positive IgG λ-type M protein, and MGUS was diagnosed in conjunction with bone marrow smear and flow cytometry.